Getting Played - Silberg, David; Vivica, A. Fox.; Bill Bellamy; Carmen Electra; Stacey Dash; Kathy Najimy (New Line Home Video U.S.A, 2005)
Welcome to the new players club where everyone's in on the game! Vivica A. Fox Carmen Electra and Stacy Dash star as three smart and sexy friends fed up with being played by the men in their lives. To prove that all men are predictable and easily seduced this hot trio decides to play by a new set of rules. They enter into a wild contest of seduction to convince one lucky man that he's living a dream... but what the girls don't realize is that their mark is in onto their game and he's got a few plays of his own.
Languages : English, Turkish Subtitle: Turkish
Keywords: Comedy